THE EFFECT OF IMPLEMENTING GOOD CORPORATE GOVERNANCE ON COMPANY PERFORMANCE IN BANKING COMPANIES LISTED ON THE IDX - Erfina Fernanda; Heri Widodo (Antis Publisher, 2025)
Objective: This research aims to examine the effect of implementing good corporate governance (GCG) on company performance, especially in the banking sector listed on the IDX for the 2020–2022 period. The independent variables used are the Independent Board of Commissioners, Board of Directors, Audit Committee, and Managerial Ownership with the dependent variable Return On Assets (ROA). Method: The sampling technique used was purposive sampling and a sample of 81 was obtained. Data collection used secondary data taken from www.idx.co.id. The data analysis technique uses linear multiple regression analysis. Result: The research results show that the independent board of commissioners, board of directors, and audit committee have a significant positive influence on company performance. In contrast, managerial ownership did not show a significant influence on company performance in this study. Novelty: The novelty of this study lies in its specific focus on the banking sector listed on the IDX during the 2020–2022 period, providing empirical evidence of how different components of good corporate governance contribute to company performance, particularly emphasizing the stronger impact of institutional governance mechanisms compared to managerial ownership.